The Silent Classroom: The Impact of Smartphones and a Social Studies Teacher's Response. Issue 3 (4th May 2019) - D. Siebert, Molly
Abstract: The accelerated ownership and usage of smartphones and social media presents multiple issues for educators. There is a relationship between smartphones and (a) academic achievement, (b) engagement, and (c) mental health. The purpose of this literature review is to investigate the impact of smartphones and social media on students and how curriculum can best prepare youth for democratic citizenship. The case studies included in this review span beyond the United States due to the insightful research that has been conducted in various locations across the globe. When reviewing the literature, a few themes emerged. First, students who struggle the most academically are the ones who benefit most from the absence of a smartphone. Second, students of color are spending more time on social media and due to the increased exposure to racial discrimination online, academic motivation is decreasing for many of these students. Third, many researchers encourage schools to develop policies to limit smartphone use in the classroom. Finally, it is evident that the social studies curriculum needs to be expanded to include digital citizenship, media literacy, and the potential negative impact of smartphones and social media on students.